Modeling Effect of Different Pollutant Sources on Water Quality of Atrak River Using QUAL2KW Model - Mohammad Mirnezhad; Ghasem Zolfaghari (محیط زیست و مهندسی آب, 2024)
Rivers, where there is a large concentration of human activities, receive a large amount of pollution. The purpose of this study was to monitor and model the water quality of the Atrak River in the geographical area of ​​Bojnurd and to investigate the effect of polluting sources on the river using the QUAL2KW model. After the field visit a study area of ​​33 km length, with 16 reaches, 11 main sampling stations, 10 sampling stations of point sources, and 2 sampling stations of non-point sources were selected and specified. In this study, four qualitative parameters of temperature, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD) were measured and simulated in the spring of 2022. Hydraulic geometric data, qualitative data and meteorological data were entered into the QUAL2KW model. The simulation error was calculated using Absolute Mean Error (AME), Mean Absolute Percentage Error (%MAPE), and Root Mean Squared Error (%RMSE). The RMSE for temperature, DO, BOD and COD parameters was determined as 3.68, 4.51, 6.5, and 4.47, respectively. According to the amount of calculated errors, it was found that the QUAL2KW model had a very good accuracy in the qualitative simulation of Atrak River.